STELLER AS AN INSTRUCTIONAL MEDIA IN TEACHING WRITING NARRATIVE TEXT - Via Ayu Silvia (Journal of English Education Program (JEEP), 2020)
AbstractThis article is reported on the teacher uses steller as an instructional media in teaching writing narrative text. It also investigated the teacher’s perception towards steller application in teaching writing narrative text and the students’ perceptions toward steller application in writing narrative text. Steller is a free storytelling apps which lets the users to create story with combining text, images or video. In conducting this research the researchers used qualitative research in which case study was employed to collect the data from participants. The participants in this research were an English teacher and thirty six of tenth grade students at SMAN 1 Pangandaran. This research used triangulation data techniques such as observation, interview and questionnaire. The result of study shows there are several steps in teaching writing narrative text by using steller in the class. Moreover, the teacher and students gave positive perceptions toward steller application in teaching and writing narrative text. Finally, the researchers are recommended the future researcher to conduct the research with similar topic but using another kind of instructional media.Keywords: Instructional Media, Teaching Media, Digital Story, Steller, Narrative text